Delayed responses of major stored-product beetle species after exposure to an alpha-cypermethrin-coated net. (January 2023) - Agrafioti, Paraskevi; Rumbos, Christos I.; Paloukas, Yiannis Z.; Arvanitakis, George; Athanassiou, Christos G.
Abstract: Carifend® is an alpha-cypermethrin-coated net that has been evaluated with success for the control of insects that infest stored tobacco. More recent data indicate that nets that contain insecticides can be further utilized against a wide range of stored-product insect species in different application scenarios. The aim of the current study was to evaluate Carifend® against adults of the rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), the confused flour beetle, Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae), the saw-toothed grain beetle, Oryzaephilus surinamensis (L.) (Coleoptera: Silvanidae), the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrychidae), and the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). Adults of these species were exposed to dishes containing Carifend® for 2, 8 and 24 h, and then they were transferred to untreated dishes, where mortality was recorded 7 d later. In most of the cases, the duration of the initial exposure increased mortality, but, in general, mortality was further increased after the termination of the post-exposure interval. Among the species tested, T. confusum was found to be the least susceptible to Carifend®. For instance, the mortality level was 5.5% for T. confusum even 7 d after exposure, while for P. truncatus it was 100%. The results of the present study clearly demonstrate that Carifend® can be an effective tool against a wide range of major stored-product beetle species, even at exposures that last for <24 h. Highlights: Carifend®, an insecticide-coated net, has been tested for the control of adults of six stored-product beetle species. There was a considerable delayed mortality 7 days after the end of the exposure for all species. Among the species tested, Tribolium confusum was by far the least susceptible species to Carifend®. Can be effective for the control of a wide range of stored-product insect species.